FRI0083 Large joint damage after 8 years of das-steered treatment in early rheumatoid arthritis (RA) patients. (23rd January 2014) - van den Broek, M.; Dirven, L.; Kroon, H.; Westedt, M.; Gerards, A.; Kerstens, P.; Huizinga, T.; Lems, W.; Allaart, C.
Abstract : Background: In non-disease activity steered treated RA cohorts, large and small joint damage were highly correlated. Large joint damage was associated with disability. Local inflammation predicts later damage in small joints. Objectives: To assess the association of radiological damage in the large joints with small joint damage and functional ability after 8 years of disease activity steered treatment, and to investigate whether local swelling and pain are predictive of later large joint damage. Methods: After 8 years of follow-up, radiographs of the large joints were made for all patients still under follow-up in the BeSt study, a randomized controlled trial with a disease activity (DAS≤2.4) steered protocol. These were scored by an experienced radiologist (HK) using the Larsen score (ranging from 0-5 in each joint). Radiographs of the small joints were scored using the Sharp/vd Heijde score (SHS). Disability was assessed using the Health Assessment Questionnaire (HAQ). The association between small joint damage progression and large joint damage (total Larsen score without wrists ≥1) was assessed using multivariate logistic regression analyses. A multivariate logistic regression analysis was then used to investigate the association between large joint damage (total Larsen score in tertiles) and functional disability. The association between local swelling and/or pain in a large joint in the first 2 years of treatment and damage in that same joint after 8 years (Larsen score ≥1) was assessed using generalized estimating equations. Results: Radiographs were available in 290 patients. Joint damage was observed in 64/532 (12%) shoulders, 51/538 (9.5%) elbows, 141/541 (26%) wrists, 141/541 (26%) hips, 95/528 (18%) knees and 39/544 (7%) ankles. Seven percent of the patients had one or more joint prostheses, placed because of primary osteoarthritis (50%), secondary osteoarthritis (35%), or fractures, dysplasia or other (15%). Small joints damage progression after 8 years ≥5 points and ≥15 points SHS were independently associated with a total Larsen score (not counting wrists) ≥1, with odd ratios of 2.0 (95% CI: 1.1-3.8) and 2.6 (95% CI: 1.2-5.6), respectively. Patients with a total Larsen score in the highest tertile (≥4) had a higher risk of functional impairment (HAQ ≥1) compared to patients in the lowest tertile (Larsen score of 0), with an OR of 2.5 (95% C.I. 1.01-6.1). Local large joint swelling at least once in the first 2 years or treatment was independently associated with later joint damage of that joint, with an OR of 1.8 (95%C.I. 1.3-2.3), as were persistent (≥2 consecutive visits) swelling and persistent tenderness: ORs 2.5 (1.8-3.4) and 1.4 (1.05-1.9). Conclusions: After 8 years of DAS≤2.4 targeted treatment, large joint damage was associated with damage in the small joints and with functional disability. Early local swelling and tenderness were predictive of large joint damage. These results confirm that early suppression of disease activity using DAS-steered treatment is important to prevent later disability. Disclosure of Interest: M. van den Broek Grant/Research support from: Dutch College of Health Insurances, Centocor inc and MSD (formerly Schering Plough), L. Dirven: None Declared, H. Kroon: None Declared, M. Westedt: None Declared, A. Gerards: None Declared, P. Kerstens: None Declared, T. Huizinga: None Declared, W. Lems: None Declared, C. Allaart: None Declared